Penerapan TAM Dalam Inovasi Pelayan Publik “Pak RT Suka Asik” Di Kabupaten Magetan - Agus Heru Maryanto; Sri Setyo Iriani; Sanaji Sanaji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Digital transformation of public services is one of the targets of the Government in realizing good governance in the era of digitalization. The